Flexible ring polymers in an obstacle environment: Molecular theory of linear viscoelasticity - Iyer, Balaji V. S.; Lele, Ashish K.; Juvekar, Vinay A. (Physical Review E, 2006)
We formulate a coarse-grained mean-field approach to study the dynamics of the flexible ring polymer in any given obstacle (gel or melt) environment. The similarity of the static structure of the ring polymer with that of the ideal randomly branched polymer is exploited in formulating the dynamical model using aspects of the pom-pom model for branched polymers. The topological constraints are handled via the tube model framework. Based on our formulation we obtain expressions for diffusion coefficient D, relaxation times tau, and dynamic structure factor g(k,t). Further, based on the framework we develop a molecular theory of linear viscoelasticity for ring polymers in a given obstacle environment and derive the expression for the relaxation modulus G(t). The predictions of the theoretical model are in agreement with previously proposed scaling arguments and in qualitative agreement with the available experimental results for the melt of rings.

Blob-spring model for the dynamics of ring polymer in obstacle environment - Lele, Ashish K.; Iyer, Balaji V. S.; Juvekar, Vinay A. (XVTH International Congress on Rheology - the Society of Rheology 80th Annual Meeting, Pts 1 and 2, 2008)
The dynamical behavior of cyclic macromolecules in a fixed obstacle (FO) environment is very different than the behavior of linear chains in the same topological environment; while the latter relax by a snake-like reptational motion from their chain ends(1) the former can relax only by contour length fluctuations since they are endless.(2) Duke, Obukhov and Rubinstein proposed a scaling model (the DOR model) to interpret the dynamical scaling exponents shown by Monte Carlo simulations of rings in a FO environment.(2) We present a model (blob-spring model) to describe the dynamics of flexible and non-concatenated ring polymer in FO environment based on a theoretical formulation developed for the dynamics of an unentangled fractal polymer.(3) We argue that the perpetual evolution of ring perimeter by the motion of contour segments results in an extra frictional load. Our model predicts self-similar dynamics with scaling exponents for the molecular weight dependence of diffusion coefficient and relaxation times that are in agreement with the scaling model proposed by Obukhov et al.(2).
15th International Congress on Rheology/80th Annual Meeting of the Society-of-Rheology, Monterey, CA, AUG 03-08, 2008
Keywords: fractal polymer dynamics; linear viscoelasticity; ring polymer dynamics

Self-diffusion coefficient of ring polymers in semidilute solution - Iyer, Balaj V. S.; Shanbhag, Sachin; Juvekar, Vinay A.; Lele, Ashish K. (Journal of Polymer Science Part B-Polymer Physics, 2008)
In a topologically constraining environment the size of a flexible nonconcatenated ring polymer (macrocycles) and its dynamics are known to differ from that of linear polymers. Hence, the diffusion coefficient of ring polymers can be expected to be different from linear chains. We present here scaling arguments for the concentration and molecular weight dependence of self-diffusion coefficient of ring polymers in semidilute solutions, and show that contrary to expectations these scaling relations are identical to what is known for linear polymers. At higher concentrations excluded volume interactions arising from possibilities of segmental overlap can become effective for large ring polymers. In this regime the diffusion coefficient of large ring polymers shows a relatively weaker dependence on concentration and molecular weight. (C) 2008 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys 46: 2370-2379, 2008
Keywords: Diffusion; Macrocycles; Monte Carlo simulation

Self-similar dynamics of a flexible ring polymer in a fixed obstacle environment: a coarse-grained molecular model - Iyer, Balaji V. S.; Lele, Ashish K.; Juvekar, Vinay A.; Mashelkar, Raghunath Anant (Industrial & Engineering Chemistry Research, 2009)
In this contribution we concern ourselves with an interesting problem, namely, the dynamics of ideal flexible ring polymers constrained in tin array of fixed obstacles. The fundamental issue in this problem is to understand how a topologically constrained polymer chain is able to relax its conformation in the absence of chain ends. The key physics was provided in tin elegant scaling theory by Rubinstein and co-workers (Obukhov, S. P; Rubinstein, M.; Duke, T. Dynamics of a Ring Polymer in a Gel. Phys. Rev. Lett. 1994, 73, 1263-1267). In this work we develop a coarse-grained mean-field model based oil the physical arguments of the scaling theory and derive constitutive relations for rings in fixed obstacle and melt environments. The model is composed of three distinct steps. In the first step the dynamics of an arbitrary section of a ring chain is worked out based oil fractal Blob-Spring (BS) dynamics, and the center of mass diffusion and the relaxation spectrum of this section are determined. In the second step the center of mass diffusion obtained using the BS dynamics is used to model the one-dimensional diffusion of the section in a topologically constrained environment. In the final step we invoke the idea of dynamic self-similarity and argue that the dynamics described in the first and the second step, for any arbitrary section of the chain, applies to all sections of the chain. The constitutive relation is obtained consequently as the superposition of dynamic response of all sections of the ring chain.

Solid suspension and liquid phase mixing in solid-liquid stirred tanks - Sardeshpande, Madhavi V.; Sagi, Aparna R.; Juvekar, Vinay A.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2009)
Stirred tanks are widely used in chemical process industries for catalytic reactions, dissolution of solids, crystallization, and so oil. In designing and optimizing such processes, suspension quality Of Slurry is an important parameter. Suspension quality depends upon complex interactions of impeller generated flow, turbulence, and solid loading. Most of the earlier work on solid suspension focuses Oil identifying critical impeller speed for just suspension of solids (N(js)). In this study, apart from N(js) aspects like cloud height and liquid phase mixing in solid-liquid suspensions were also studied A new way of characterizing solid-liquid suspensions and liquid phase mixing using nonintrusive wall pressure fluctuation measurements has been developed. Systematic experimental data on N(js), cloud height, power consumption, mixing time, and circulation time over a range of solid volume fraction and impeller speeds have been presented here. The results and discussion presented here will have useful implications for designing solid-liquid stirred tanks.

Hysteresis in cloud heights during solid suspension in stirred tank reactor: experiments and CFD simulations - Sardeshpande, Madhavi V.; Juvekar, Vinay A.; Ranade, Vivek V. (Aiche Journal, 2010)
Solid suspension in stirred tank reactor is widely used in process industries for catalytic reactions, dissolution of solids, crystallization, and so on. Suspension quality is a key issue in design and operation of stirred reactor and its determination is not straight forward. Cloud height measurements of solid suspension provide a relatively simple way to quantify quality of suspension. In this work, experiments were carried out to quantify variation of cloud heights with impeller speed and particle characteristics. These measurements were carried out using visual observations, image analysis, and ultrasound velocity profiler techniques. The obtained data demonstrated the existence of hysteresis in cloud heights with respect to impeller speed. Apart from possible applications in reducing power required for achieving desired solid suspension quality, the existence of hysteresis also provides a new way to evaluate computational fluid dynamics (CFD) simulations of solid liquid flows in stirred vessels. An attempt was made to capture observed hysteresis in cloud heights in CFD simulations. The simulated results were compared with the experimental data. The presented models and results (experimental and computational) will he useful for simulating complex solid liquid flows in stirred reactors. (C) 2010 American Institute of Chemical Engineers AIChE J, 56: 2795-2804, 2010
Keywords: CFD; hysteresis in cloud height; solid velocity profiles

Solid suspension in stirred tanks: UVP measurements and CFD simulations - Sardeshpande, Madhavi V.; Juvekar, Vinay A.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
Suspension of solids in stirred reactor is widely used for catalytic reactions, dissolution, etc. Quality of solid suspension is an important parameter required for the reliable design, optimum performance, and scale up of the system. Quality of suspension depends on local characteristics of solid velocity and hold up profiles. The present work was focused on investigating quality of solid suspension using ultrasound velocity profiler (UVP) measurements and CFD simulations. The slip velocity measurements carried out with UVP were used to evaluate different drag correlations used in CFD simulations. Results discussed in this work would be useful for extending the applications of CFD models for simulating large stirred slurry reactors.
Keywords: CFD; drag coefficient; solid suspension; solid-liquid velocities; UVP

Effect of plug temperature on the strain and thickness distribution ofcomponents made by plug assist thermoforming - Marathe, D.; Rokade, D.; Azad, Lal Busher; Jadhav, Kishor; Mahajan, Sunil; Ahmad, Zubair; Gupta, S.; Kulkarni, S.; Juvekar, Vinay A.; Lele, Ashish K. (International Polymer Processing, 2016)
Plug temperature is a key parameter affecting the thickness distribution of thermoplastic components made by plug assist thermoforming. For a specified pair of plug and plastic sheet, the variation in plug temperature can alter the coefficient of friction (COF) between the pair. We show here how the temperature dependence of COF influences the nature and extent of biaxial stretching of the sheet and consequently the thickness distribution of the thermoformed component. In the present study, high impact polystyrene (HIPS) sheets were thermoformed into axisymmetric cups using a plug-assist process in which the aluminum plug temperature (T-plug) was varied from ambient to above the glass transition temperature of HIPS (similar to 100 degrees C). Biaxial strain maps on the surfaces of the formed cups were measured and quantified using Grid Strain Analysis (GSA). Thickness distributions of the cups were also measured. Temperature dependent COF between HIPS and aluminum was determined independently using a rotational rheometer. The measured COF was low for T < 100 degrees C, whereas it increased appreciably at and above 100 degrees C. We conclude that when T-plug < 100 degrees C the HIPS sheet slips on the plug during forming, and this results in biaxial stretching of the base and walls of the formed cup. In contrast for T-plug > 100 degrees C, a significant reduction in the magnitude of slip is expected. Here the sheet is gripped at the clamp and by the plug during forming which causes reduced biaxial stretching of the base and increased uniaxial stretching of the walls of the cup. Simulations of plug-assist thermoforming using a temperature dependent COF showed qualitative agreement with the GSA data thereby supporting our inferences.